The Flourishing of Indonesian Conspicuous Consumption in the Digital World and Its Effects on the Evolution of Hijrah Movements - Masni, Melly (Jurnal Sosiologi Agama, 2025)
This study explores the intersection of conspicuous consumption and the Hijrah movement within Indonesia's socio-cultural and economic transformations. The rise of the middle class, coupled with the proliferation of social media, has amplified conspicuous consumption, where symbols of wealth and social status are prominently displayed. In this context, religiosity emerges as a unique form of status signaling, referred to in this study as "conspicuous consumption of piousness." Simultaneously, the contemporary Hijrah movement has gained momentum, marked by its emphasis on personal transformation and lifestyle adjustments rather than political activism. Utilizing qualitative content analysis, this research reveals a reciprocal relationship between conspicuous consumption and the Hijrah movement. It highlights how middle-class anxieties and aspirations provide fertile ground for the Hijrah movement’s growth, while the movement itself fosters a platform for displaying religiosity as a marker of both piety and modernity. These findings contribute to theoretical debates on conspicuous consumption by extending its scope to include immaterial aspects and religious identities in a non-Western context, offering critical insights into the evolving dynamics of consumerism and religiosity.